2005
DOI: 10.3917/sta.067.0059
|View full text |Cite
|
Sign up to set email alerts
|

Position des pieds et paramètres stabilométriques

Abstract: Résumé L’objectif de notre étude était de compléter et d’approfondir les travaux déjà réalisés concernant les effets de la position des pieds sur l’équilibre orthostatique. Nous avons testé une population de 25 sujets masculins sur 16 positions de pieds (combinaisons de 4 écartements et 4 angles d’ouverture) et suivant les conditions expérimentales de l’Association Française de Posturologie. L’augmentation de la surface du polygone de sustentation a entraîné une amélioration de l’équilibre orthostatique. Cette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This study used a customized support base compared to selected studies that use a standardized support base. In their study, Mouzat et al [28] demonstrated that the increase in the spacing of the opening angle of the feet is correlated with an improvement of the static equilibrium. The use of a personalized support base is therefore sensible to allow subjects to place themselves in a position where they feel stable rather than constrain them in a potentially unbalanced position.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This study used a customized support base compared to selected studies that use a standardized support base. In their study, Mouzat et al [28] demonstrated that the increase in the spacing of the opening angle of the feet is correlated with an improvement of the static equilibrium. The use of a personalized support base is therefore sensible to allow subjects to place themselves in a position where they feel stable rather than constrain them in a potentially unbalanced position.…”
Section: Discussionmentioning
confidence: 95%
“…The sensory system also undergoes involutions during aging that are visually reflected by a decrease in contrast sensitivity, accommodation capacity, and / or acuity degradation [38,39]. The elderly person will then have difficulty in perceiving the textures, the shapes and the colors of the objects but also the orientation and the speed of the movements [28].…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the finding of the study [19] showing that average preferred foot position was 0.17 m between heel centers, with an angle of 14 degrees between the long axes of the feet and that foot placement influences stabilizing reactions. It is found also that the inner feet distance have a stabilizing effect [20]. This in is explained by the fact that the increase of the distance between feet serves the increase of support base, so this induced an improvement in orthostatic equilibrium.…”
Section: B Proprioceptive Entry Effectsmentioning
confidence: 88%
“…This study used a customized support base compared to selected studies that use a standardized support base. In their study, Mouzat et al (2005) [28] demonstrated that the increase in the spacing of the opening angle of the feet is correlated with an improvement of the static equilibrium. The use of a personalized support base is therefore sensible to allow subjects to place themselves in a position where they feel stable rather than constrain them in a potentially unbalanced position.…”
Section: Discussionmentioning
confidence: 98%
“…The sensory system also undergoes involutions during aging that are visually reflected by a decrease in contrast sensitivity, accommodation capacity, and / or acuity degradation [38,39]. The elderly person will then have difficulty in perceiving the textures, the shapes, and the colors of the objects but also the orientation and the speed of the movements [28]. Regarding the proprioceptive system, all receptors change with age.…”
Section: Discussionmentioning
confidence: 99%